Analyzers of charged particles flows with different functional capabilities - Saulebekov, A.O.; Kambarova, Zh.T. (IOP Conference Series: Materials Science and Engineering, 2017)
Parameters of instruments developed on the basis of previously calculated different electron-optical systems for the analysis of charged particle flows were considered in the present work. Recommendations for their application in various fields of electron spectroscopy for the analysis of a solid surface were given.
Keywords: Analyzers; charged particles flows; with different functional capabilities